A Discourse on Jubilee among Indonesian Pentecostals and Charismatics - Jairus Hasugian (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
This study aims to describe the Pentecostal-Charismatic discourse about the Jubilee. The study is a qualitative-descriptive study and used literature study approach. Sampling was conducted to Pentecostal-Charismatic circles in several Pentecostal-Charismatic denominations. The data sources are documents in the forms of sermons, magazines, brochures, Jubilee Committee work reports, articles, liturgies, and songs about the Jubilee. Results show that the Pentecostal-Charismatic perspective regarding the Jubilee was generally different from that of the non-Pentecostal-Charismatic. According to Pentecostals-Charismatics, slave liberation meant to be restoration of a man from sin, from shackles of bondage of the evil one, from sickness, from weakness, and from inner wounds & want/poverty by the power of Jesus’ cross; Then, the land that must be returned to its original owner was defined as the return of humans to their right position, that is, before they fall into sin. Regarding the relevance of land regulations in the Jubilee was the arrangement of the organizational structure or church management, in which the older generation began to retire and was replaced by the younger generation; whereas the rest itself was intended for humans to be able to have a fellowship with God, so that they do not get greedy and can appreciate others’ property.